Strategi Usaha Sambal Goreng Udang Pete : Meningkatkan Kesejahteraan Masyarakat Bengawan, Juata Permai - Nurul Hidayat; Nabila Afdaliyah; Adrian Maulana; Nuprianti Nuprianti; Jasmin Putra Pratama; Natalia Natalia; Sukmawati Sukmawati (STIKes Ibnu Sina Ajibarang, 2025)
Shrimp is one of the marine resources with significant economic potential, particularly in tropical regions. The utilization of shrimp can contribute substantially to the economy of coastal communities. This study aims to analyze the economic potential of shrimp and its utilization by coastal communities in tropical regions. The results of the study indicate that shrimp has significant economic potential, with production values reaching hundreds of millions of dollars per year. However, the utilization of shrimp by coastal communities is still suboptimal due to limited market access, lack of knowledge on shrimp processing technology, and inadequate government support. This study recommends several strategies to enhance the utilization of shrimp by coastal communities, including market infrastructure development, training on shrimp processing technology, and increased government support.